Multiple functions of the crustacean gill: osmotic/ionic regulation, acid-base balance, ammonia excretion, and bioaccumulation of toxic metals - Henry, Raymond P.; Lucu, Cedomil; Onken, Horst; Weihrauch, Dirk (Frontiers in Physiology, 2012)
The crustacean gill is a multi-functional organ,and it is the site of a number of physiological processes, including ion transport, which is the basis for hemolymph osmoregulation; acid-base balance; and ammonia excretion. The gill is also the site by which many toxic metals are taken up by aquatic crustaceans, and thus it plays an important role in the toxicology of these species. This review provides a comprehensive overview of the ecology, physiology, biochemistry, and molecular biology of the mechanisms of osmotic and ionic regulation performed by the gill. The current concepts of the mechanisms of ion transport, the structural, biochemical, and molecular bases of systemic physiology, and the history of their development are discussed. The relationship between branchial ion transport and hemolymph acid-base regulation is also treated. In addition, the mechanisms of ammonia transport and excretion across the gill are discussed. And finally, the toxicology of heavy metal accumulation via the gill is reviewd in detail.